Internet Memes: An Approach to Building Customer Relationships in the Digital Age - Putra, Made Dwi Pradnyana; Hastjarjo, Sri; Satyawan, Ignatius Agung (International Journal of Social Science and Business, 2025)
Using internet memes as a marketing tool is one strategy that every company can apply to market their products and reach their consumers in the current digital era. The aim of this research is to analyze the construction of meme messages and explain the function of using these memes in marketing on Netflixid and Vidiodotcom’s Instagram accounts. This research uses the concepts of content marketing and internet memes as a reference for analysis. The method used in this research is qualitative content analysis. A total of 25 uploads from each @netflixid and @vidiodotcom were analyzed using the meme dimension analysis model, including content, form, and stance. Based on the content analysis of dimensions in memes, the form dimension shows the most differences. Meme creators at each company take snippets of films, dramas, and series that are their own products. In terms of shape dimensions, there has been a change from what was originally a video format to a photo. The narrative built on memes is also different from the narrative in the original source. Apart from that, there are differences in the function of each meme in the two companies. On Netflixid Instagram account, memes are used to build relationships using the soft selling method. Meanwhile, Vidiodotcom’s Instagram account shows how memes are designed with the aim of building consumer relationships using soft selling and hard selling method.